2014
DOI: 10.1007/s00441-014-1905-x
|View full text |Cite
|
Sign up to set email alerts
|

Primary alveolar macrophages exposed to diesel particulate matter increase RAGE expression and activate RAGE signaling

Abstract: Receptors for advanced glycation end-products (RAGE) are members of the immunoglobulin superfamily of cell-surface receptors implicated in mechanisms of pulmonary inflammation. In the current study, we test the hypothesis that RAGE mediates inflammation in primary alveolar macrophages (AMs) exposed to diesel particulate matter (DPM). Quantitative RT-PCR and immunoblotting revealed that RAGE was up-regulated in Raw264.7 cells, an immortalized murine macrophage cell line and primary AMs exposed to DPM for 2 h. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
1
14
0
1
Order By: Relevance
“…The release of IL-1-like cytokines promotes the activation of NF-κB 28 , which is at the basis of inflammatory pathways. In support of this, several authors demonstrated that soot particles can lead to NF-κB activation in both macrophage/monocyte cell lines and a human epithelial cell line (A549) 29 30 .…”
Section: Discussionmentioning
confidence: 80%
“…The release of IL-1-like cytokines promotes the activation of NF-κB 28 , which is at the basis of inflammatory pathways. In support of this, several authors demonstrated that soot particles can lead to NF-κB activation in both macrophage/monocyte cell lines and a human epithelial cell line (A549) 29 30 .…”
Section: Discussionmentioning
confidence: 80%
“…One of the most consistent associations of RAGE in the literature is with inflammation and activation innate signal transduction pathways. The activation of NF‐κB and the MAPK signaling pathway and the resulting production of cytokines like TNF‐α are observed routinely, and has been reported for AGE‐treated RAW 264.7 cells, 66–68 peritoneal macrophages, 69 BMDM, 70 and THP‐1 cells 68,71 or alveolar macrophages exposed to diesel particulate matter 18 or cigarette smoke extract 22 that contain RAGE ligands. Different AGE structures have different intrinsic abilities to induce cytokines in human peripheral blood mononuclear cells (PBMCs) 8,30 .…”
Section: Role Of Rage In Inflammationmentioning
confidence: 89%
“…The lung is a key anatomical site for RAGE protein expression and within the lung of mice, isolated alveolar macrophages express less RAGE than whole lung tissue in terms of mRNA and protein 23 . Expression of RAGE in alveolar macrophages can be increased by external stimuli such as diesel particulate matter 18 or cigarette smoke extract 22 that may be encountered in lung. Hypoxia has also been shown to induce RAGE expression in human macrophage‐like THP‐1 cells 24 .…”
Section: Introductionmentioning
confidence: 99%
“…RAGE is a strong activator of the proinflammatory transcription factor NF-κB (nuclear factor-κB) and thereby represents an important signaling molecule in the innate immune system. In the lung, RAGE is selectively present in AECI, in some endothelial cells of larger blood vessels, and in alveolar macrophages [ 124 – 126 ]. Immunoelectron microscopic studies revealed the presence of RAGE at the basolateral aspect of AECI of mouse, rat, and human lung [ 124 , 127 ] opposite to the common basement membrane of the air–blood barrier.…”
Section: Putative Signaling Pathways Connected With Aeci Cellsmentioning
confidence: 99%